الحاجات النفسية في ضوء نظرية تحديد الذات وعلاقتها بالسعادة لدى طلبة جامعة اليرموك - الزغول، رافع عقيل; عبدالرحمن، عبدالسلام; الدبابي، خلدون ابراهيم (الجامعة الأردنية - عمادة البحث العلمي, 2019)
The current study aimed to investigate the psychological needs in view of self determination theory and its relationship to happiness among Yarmouk University students. To achieve this aim, the psychological needs scale of Dice & Ryan and Oxford’s Inventory of happiness were employed. The sample consisted of 339 students who were selected on availability basis during the first semester 2015/2016. The results of the study showed that there was a statistically significant correlation between all of the psychological dimensions (autonomy, competence and relatedness) and happiness. Additionally, the results showed no statistically significant differences that could be attributed to sex in all dimensions except relatedness in favor of females. The results also revealed no statistically significant differences in all dimensions of psychological needs except competence in favor of humanities. Furthermore, the study showed that the degrees of happiness differ by sex and major in favor of females and humanities. The study recommended to include more emphasis to be given to psychological needs for its significant impact on achieving happiness for college students.
هدفت الدراسة إلى الكشف عن الحاجات النفسية في ضوء نظرية تحديد الذات وعلاقتها بالسعادة لدى طلبة جامعة اليرموك ولتحقيق هدف الدراسة استخدم مقياس الحاجات النفسية لديسي ورايان، وقائمة أكسفورد للسعادة، وتكونت عينة الدراسة من (339) طالبا وطالبة في الفصل الدراسي الأول من العام 2015/2016، تم اختيارهم بالطريقة المتيسرة، أظهرت النتائج وجود علاقة ارتباطية دالة إحصائياً بين جميع أبعاد الحاجات النفسية (الاستقلال، والكفاءة، والانتماء) والسعادة، أما فيما يتعلق باختلاف الحاجات وفق الجنس، فقد أظهرت عدم وجود فروق دالة إحصائياً تعزى للجنس في جميع الأبعاد باستثناء الانتماء، وكان لصالح الإناث، وفيما يتعلق باختلافها وفق التخصص فقد أظهرت عدم وجود فروق دالة إحصائيا في جميع الأبعاد باستثناء الكفاءة وكان لصالح التخصصات الإنسانية. وفي حين أظهرت الدراسة فروقاً في درجات السعادة وفق الجنس والتخصص لصالح الإناث والتخصصات الإنسانية. وقد توصلت الدراسة إلى جملة من التوصيات أبرزها زيادة الاهتمام بتلبية الحاجات النفسية نظراً لأهميتها في تحقيق السعادة.
Keywords: الصحة النفسية -- الرعاية الإجتماعية -- الحاجات النفسية -- الذات -- السعادة -- التعليم الجامعي -- طلاب الجامعات -- جامعة اليرموك -- الأردن -- المجتمع الأردني -- مستخلصات الأبحاث